EGG CHICKEN RACE PRICE VOLATILITY IN INDONESIA BEFORE AND DURING COVID-19 PANDEMIC - Putri Feronika Girsang; Hery Toiba; Syafrial Syafrial (Agricultural Socio-Economics Journal, 2023)
Understanding about dynamics of the price and volatility of a variety of food has gotten enough big attention in life Public because experience fluctuation sharp price consequences of turmoil economies. Crisis finance COVID-19 is one of the conditions crisis economy big problems experienced by Indonesia which triggered happening fluctuation the price is not stable (volatility) at producer level and also at consumer level. one ingredient food that has fluctuation price moment the COVID-19 pandemic is ingredient food egg chicken race. The study analyzed the volatility egg chicken race in Indonesia before and during the COVID-19 pandemic in Indonesia. The study used weekly egg chicken race price data at the producers and consumers level from March 2018-March 2022. The secondary data was obtained through Sistem Informasi Pasar Online Nasional-Ternak (SIMPONI-Ternak) by the Ministry of the Agriculture Republic of Indonesia. The analytical methods used in this study were Generalized Autoregressive Conditional Heteroscedasticity (GARCH) and autoregressive conditionally heteroscedastic approach (ARCH). The findings showed that the price of egg chicken race at producers and consumers level before the COVID-19 pandemic is categorized as a low volatility category and also at producer level during COVID-19 pandemics, while at the consumer level during COVID-19 pandemic is classified as high volatility category. Thus the research this has contributed is as follows. First, useful for designing policies with intervention to help food to the right community and provide regulation prices as an effort to repair prices price in reach stability price egg chicken race post the COVID-19 pandemic is good at the level of producer nor consumer. Second, evaluate the implication performance sector egg chicken race before and during COVID- 19 for destination development sustainable.